2020
DOI: 10.1021/acs.chemmater.9b04665
|View full text |Cite
|
Sign up to set email alerts
|

Local Structure Evolvement in MOF Single Crystals Unveiled by Scanning Transmission Electron Microscopy

Abstract: The response of metal−organic frameworks (MOFs) toward external stimuli, such as light, heat, and electrons, usually involves a local change in their structures. Although diffraction methods allow for monitoring of the overall dynamics of the crystal structure, the local environment on each crystal and specific position within the crystal remains largely unknown. Here, the collective change in the pores of MOF single crystals was visualized by scanning transmission electron microscopy (STEM) with an interpreta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 38 publications
2
44
0
Order By: Relevance
“…In particular, porous materials like metal-organic frameworks (MOFs) are very suitable for this technique due to their sensitivity to electron beam. Under optimized imaging conditions, it can be expected that, the nodes, the organic linkers, defects as well as the metal species encapsulated inside the MOF structure can be clearly imaged, which will provide useful information to understand the details in the MOF materials at atomic and molecular level [69][70][71] . For example, the local structural evolution of a MIL-101 MOF sample under electron beam irradiation has been followed by STEM-iDPC, showing the subtle changes in the molecular building blocks of the MOF backbone 71 .…”
Section: Extension Of the Stem-idpc Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…In particular, porous materials like metal-organic frameworks (MOFs) are very suitable for this technique due to their sensitivity to electron beam. Under optimized imaging conditions, it can be expected that, the nodes, the organic linkers, defects as well as the metal species encapsulated inside the MOF structure can be clearly imaged, which will provide useful information to understand the details in the MOF materials at atomic and molecular level [69][70][71] . For example, the local structural evolution of a MIL-101 MOF sample under electron beam irradiation has been followed by STEM-iDPC, showing the subtle changes in the molecular building blocks of the MOF backbone 71 .…”
Section: Extension Of the Stem-idpc Techniquementioning
confidence: 99%
“…Under optimized imaging conditions, it can be expected that, the nodes, the organic linkers, defects as well as the metal species encapsulated inside the MOF structure can be clearly imaged, which will provide useful information to understand the details in the MOF materials at atomic and molecular level [69][70][71] . For example, the local structural evolution of a MIL-101 MOF sample under electron beam irradiation has been followed by STEM-iDPC, showing the subtle changes in the molecular building blocks of the MOF backbone 71 . The workflow for material synthesis and structural characterizations shown in this protocol can also be applied to other solid materials, which help to establish a reliable and comprehensive methodology to obtain structural information at atomic level by a combination of spectroscopy and electron microscopy techniques.…”
Section: Extension Of the Stem-idpc Techniquementioning
confidence: 99%
“…Unlike the smooth (1true1 1) surface, the (true1 11) surface is rough at the molecular level. The possibility that the observed surface structure was beam‐induced degradation [5h] has been ruled out by a separate electron beam irradiation experiment (Figure S8). Incomplete open cages, each of which are constructed by six out of ten STs along the [110] direction projection (Figure 2 e), are arranged regularly on the topmost surface of (true1 11) and form a large terrace with the dimension up to tens of nanometers along the [1true1 2] direction (Figure 3 a).…”
Section: Figurementioning
confidence: 99%
“…While operating the TEM for investigations of such fragile materials, the electron dose should be kept minimal to collect trustful and meaningful information. Recently, low dose cameras and detectors are being widely used for the precise imaging of MOFs down to a very local scale [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the first MOF materials that was directly imaged by TEM, and up until now, it remains a very popular MOF for TEM investigations [ 23 ]. This MOF was studied in great detail by several groups applying different techniques, among which are TEM [ 24 ], ADF-STEM [ 25 ], and iDPC [ 22 ]. Several TEM-exploiting studies of the MIL-101 loaded framework were also reported [ 17 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%